Managerial Ability and ESG Performance: A Panel Data Analysis of Non-Financial Companies on The Indonesia Stock Exchange (2018-2021) - Bramanti, Geodita Woro; Hakim, Andi; Ninglasari, Sri Yayu; Wibawa, Berto Mulia; Nareswari, Ninditya; Kunaifi, Aang; Handiwibowo, Gogor Arif (Journal of Research and Technology, 2024)
The rising implementation of Environmental, Social, & Governance (ESG) practices by companies indicates a growing commitment to responsible operations. The surge in assets allocated to ESG-focused ETFs is evident, as global investments have grown to $391 billion by 2021, a substantial increase from a mere $5 billion in 2006. Furthermore, Indonesia has witnessed a substantial surge in the number of investors who are actively engaged with companies that comply with ESG criteria. The efficacy of implementing ESG practices is intricately linked to the proficiency and expertise of managers, particularly in their decision-making and disclosure strategies. This study employed panel data regression methods to examine data from 825 non-financial companies that were publicly traded on the Indonesia Stock Exchange between 2018 and 2021. The insights were acquired utilizing the Fixed Effect Model methodology. The results indicate that the proficiency of managers does not exert a noteworthy influence on the ESG performance of companies that prioritize short-term financial benefits and exhibit limited understanding of ESG concerns, especially in sectors other than energy. Hence, it is imperative to foster effective leadership to steer companies towards holistic and sustainable strategies that transcend immediate gains, while prioritizing enduring impact and societal responsibility.